Investment protection and the investment court system in the EU–Indonesia comprehensive economic partnership - Erni Yoesry (IHSA Institute, 2026)
The reform of international investment governance has increasingly emphasized the need to balance investor protection with the regulatory sovereignty of host states. Within this context, the introduction of the Investment Court System (ICS) under the EU–Indonesia Comprehensive Economic Partnership Agreement (IEU–CEPA) represents a significant institutional shift in investment dispute settlement. However, existing studies have largely examined the ICS from a general or comparative perspective, with limited attention to its specific implications for Indonesia’s post-BIT investment policy. This study provides a contextualized legal analysis of the investment protection framework and the proposed implementation of the ICS within the IEU–CEPA. It applies a normative legal research approach based on the analysis of international agreements, legal documents, academic literature, and policy reports. The study focuses on examining the institutional design of the ICS in comparison with the traditional Investor–State Dispute Settlement (ISDS) mechanism and evaluates its potential implications for Indonesia. The findings indicate that the ICS introduces institutional improvements through the establishment of a permanent tribunal, the incorporation of an appellate mechanism, and enhanced procedural transparency, which collectively strengthen legal certainty and predictability in investment dispute settlement. However, these same features may also constrain the regulatory flexibility of the state by promoting more consistent and binding legal interpretations. As a result, the ICS does not eliminate the tension between investor protection and state sovereignty, but rather restructures it into a more institutionalized and predictable form. The study concludes that the effectiveness of the ICS framework will depend on Indonesia’s ability to manage this trade-off by strengthening institutional capacity and safeguarding national policy space. This research contributes to the discourse on international investment law reform by highlighting how institutional innovations in dispute settlement mechanisms may simultaneously enhance legal certainty while redefining the scope of state regulatory autonomy.